Pengaruh Pemanfaatan E-Learning dan Motivasi Belajar terhadap Hasil Belajar Siswa SMK Negeri 7 Medan - Purba, Debora; Nura, Alfi (Jurnal Nasional Manajemen Pemasaran dan SDM, 2022)
The problem in this study is the low learning outcomes of retail business management in class XI students of the Department of Online Business and Marketing where there are still students who have learning outcomes below the KKM. This study aims to determine the effect of using E-Learning and learning motivation on student learning outcomes at SMK Negeri 7 Medan. This research was conducted in class Xl BDP 1 and 2 SMK Negeri 7 Medan with a population of all students of class XI Online Business and Marketing, amounting to 68 people. Data was collected by means of observation, documentation and questionnaires. Then the data collected is processed using multiple linear regression with the help of SPSS Version 23 software. From the results of multiple linear regression analysis and hypothesis testing, it can be concluded that the use of E-Learning and Learning Motivation has an effect on Learning Outcomes. This can be seen from the results of multiple linear regression analysis obtained equation Y= 7,864 + 0,833X1 + 0,323X2. Furthermore, from the results of the study, it was obtained that the use of E-Learning (X1) had a positive and significant effect on learning outcomes (Y) as indicated by the t-valuecount of 3.365 > ttable 1.995 with a level of significant 0.001 < 0.05. Learning Motivation (X2) on Learning Outcomes (Y) with a t-valuecount of 2.099 > t-table 1.995 with a significant level of 0.000 <0.05. Simultaneously (F test) is indicated by theF result valuecalculated of 5.839 > Ftable 3.13 with a significant level of 0.005 < 0.05, so it can be said that the hypothesis is accepted. Based on the coefficient of determination test, it was obtained that R2 was 0.533, meaning that the percentage of the contribution of the independent variable to the dependent variable was 53.3% and the remaining 46.7% was influenced by other factors outside of this study.